Kebijakan Teknologi Reproduksi dengan Bantuan di Indonesia: Telaah Komparatif dan Teologis-Etis terhadap Permenkes Kespro No. 2 Tahun 2025 - Denni Boy Saragih; Arlina Permatasari Wiguna (Societas Dei: Jurnal Agama dan Masyarakat, 2025)
This article examines the ethical and theological implications of in vitro fertilization (IVF) in the context of Indonesia’s Ministry of Health Regulation No. 2 of 2025 on Reproductive Health. IVF is widely practiced, including among Christians, but raises moral concerns—particularly regarding the status of embryos, the freezing of surplus embryos, and their potential destruction. Using a qualitative approach with normative-comparative analysis, this article analyzes the regulation from a Christian theological perspective and compares it with Germany’s more embryo-protective policies. The theological discussion examines three positions on the moral status of the pre-implantation embryo: non-personal, pre-personal, and personal. Emphasis is placed on the personalist view, which asserts that human life begins at fertilization and must be protected from the earliest stage, i.e., an embryo is already bearer of God’s image (Imago Dei) since the inception. The article proposes an ethical-theological framework for Christian engagement with IVF, including: limiting embryo production to those intended for implantation, avoiding embryo freezing, rejecting embryo destruction, and affirming the theological meaning of children as a fruit of marital love. This work aims to serve as a contextual and responsible ethical guide for churches and Christian leaders in Indonesia.